Persepsi Mahasiswa Tentang Profesionalitas Dosen Jurusan Ushuluddin Dan Syariah STAIN Kediri Dan Korelasinya Dengan Keberhasilan Perkuliahan - Noer Hadi (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
This study focuses on the learning success and its reciprocal correlation with teacher professionalism accordingÂ to the student perspective. The present study is necessary to conduct, since as one evidence of teacherÂ professionalism, teacher certification, according to Peraturan Pemerintah Number 37 year 2009 Chapter 7, isÂ valid as long as a teacher does their assignment as teachers, and is not evaluated regularly. Meanwhile, teacherÂ evaluation, according to James H. Strongs, is considerably needed to improve teacher professionalism in orderÂ that teachers can provide the best quality learning experience to all their students.Â The data collection technique employed in the present study was questionnaire. The respondent was all studentsÂ of the Departments of Ushuludin and Syariâ€™ah, studying in semester III, V and VII who were having classes whenÂ the data were collected, with a total of 681 students. Pearson Product Moment was then employed to analyze theÂ data, since the data of the two variables were interval and normally distributed.Â The present study oncludes that, firstly, 11 (1.62%) of the students assess that the ssionalism of theirÂ teachers is very bad, 39 (5.73%) bad, 200 (29.3%) fair, 192 (19%) ood, and 13 (1.91%) very good. Secondly, 13Â (1.31%) of the students ought that the success of their learning was very bad, 44 (6.46%) bad, 192 28.19%) fair,Â 308 (45.23%) good, and 124 (28.21%) very good. Thirdly, eacher professionalism is positively correlated with theÂ learning success; the ontribution of teacher professionalism for the learning success is 33.18%, hile the otherÂ 66.82% is affected by other variables.